2015
DOI: 10.1136/bmj.h1325
|View full text |Cite
|
Sign up to set email alerts
|

Patients and healthcare conferences: what does true involvement look like?

Abstract: In the circus of healthcare conferences how can we make patients the ringmasters and not the monkeys?Anya de Iongh member, patient panel, The BMJ, Ceinwen Giles independent consultant in field of patient experience and engagement and member, patient panel, The BMJ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…8 Despite this progress, the role of patients in academic medical conferences has been poorly defined, discussed, and implemented. 9 We describe the benefits of patient partnership in academic medical conferences and how it can be enabled. We define medical conferences to include any meeting where health care issues are discussed for the purpose of educating, evaluating or improving medical care.…”
mentioning
confidence: 99%
“…8 Despite this progress, the role of patients in academic medical conferences has been poorly defined, discussed, and implemented. 9 We describe the benefits of patient partnership in academic medical conferences and how it can be enabled. We define medical conferences to include any meeting where health care issues are discussed for the purpose of educating, evaluating or improving medical care.…”
mentioning
confidence: 99%
“…8 Participants also suggested that all patients/caregivers should be named delegates in the program (with permission), acknowledged, be financially supported to attend, given a clear brief to speak on, and have the opportunity to shape the agenda of the conference and specific sessions, which have previously been suggested by patient partners. 1,11,15,26…”
Section: Discussionmentioning
confidence: 99%
“…TG conducted semi-structured interviews with participants, either face-to-face when possible or via videoconference from May to June 2018. The interview guide was developed based on a review of the literature 1,3,6,10,12,13,18,21 and discussion with investigators (Online Supplemental Item 1). All interviews were audio recorded and transcribed verbatim.…”
Section: Methodsmentioning
confidence: 99%
“…Conferences represent an opportunity for meaningful partnership with consumers to deliver this information and we have identified strategies to ensure such engagement is achievable and worthwhile (Box ). These closely align with the principles of patient involvement in conferences (accommodation, codesign, engagement, education and mentorship) as recommended in the Stanford Framework for Patient Partnership developed by Chu et al and suggestions made by consumers …”
Section: Reflectionsmentioning
confidence: 94%